2020
DOI: 10.7554/elife.60547
|View full text |Cite
|
Sign up to set email alerts
|

Label-free imaging of immune cell dynamics in the living retina using adaptive optics

Abstract: Our recent work characterized the movement of single blood cells within the retinal vasculature (Joseph et al. 2019) using adaptive optics ophthalmoscopy. Here, we apply this technique to the context of acute inflammation and discover both infiltrating and tissue-resident immune cells to be visible without any labeling in the living mouse retina using near-infrared light alone. Intravital imaging of immune cells can be negatively impacted by surgical manipulation, exogenous dyes, transgenic manipulation and ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Non-confocal AOSLO imaging of mice has allowed label-free imaging of microglia and their motility 37,38 . Some of these investigations in mice have used fluorescent markers to identify resident microglia and differentiate them from infiltrating immune cells as well as image retinal inflammation in an endotoxin induced uveitis model 39 where heterogenous immune cells, neutrophil and monocyte populations and their motility were imaged. They also showed neutrophils rolling along the venular endothelium and infiltrating monocytes and macrophages present both in vessels and extravasated into retinal tissue 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-confocal AOSLO imaging of mice has allowed label-free imaging of microglia and their motility 37,38 . Some of these investigations in mice have used fluorescent markers to identify resident microglia and differentiate them from infiltrating immune cells as well as image retinal inflammation in an endotoxin induced uveitis model 39 where heterogenous immune cells, neutrophil and monocyte populations and their motility were imaged. They also showed neutrophils rolling along the venular endothelium and infiltrating monocytes and macrophages present both in vessels and extravasated into retinal tissue 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these investigations in mice have used fluorescent markers to identify resident microglia and differentiate them from infiltrating immune cells as well as image retinal inflammation in an endotoxin induced uveitis model 39 where heterogenous immune cells, neutrophil and monocyte populations and their motility were imaged. They also showed neutrophils rolling along the venular endothelium and infiltrating monocytes and macrophages present both in vessels and extravasated into retinal tissue 39 . One of the limitations of human imaging is that we do not have the flexibility to selectively label cells, so we lack the capability to differentiate activated resident microglia from infiltrating macrophages.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 75 77 Although automated analysis workflows have simplified the lengthy and laborious process of determining cell velocities with AO-SLO, the limited FOV still requires flow analysis to be performed on a vessel-by-vessel basis. 76 A side-by-side comparison of LSCI and AO-SLO would enable LSCI-based measurements of speckle intensity to be related directly to flow velocity (at least within the individual animal) and would allow quantitative measurements of flow in vessels across the whole retina without montaging.…”
Section: Discussionmentioning
confidence: 99%
“…OCT-A is important for this analysis because the vascular plexus is used for registration of multiple scans. MLCs possess properties associated with macrophages including mobility, a ramified morphology [ 9 ], and correspondence to Cx3cr1 + cells (a macrophage marker) in mice [ 10 ]. Furthermore, we recently showed that clinical MLCs correspond to microglia, vitreal hyalocytes, and perivascular macrophages at steady state, and additionally include classical monocytes and monocyte-derived macrophages during neuroinflammation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%